A Comparison between the Modality Analyses of Two Ellen Talk Shows - Kyaw, Ae Mon (Master Program in Linguistics, Diponegoro University, 2024)
According to Systemic Functional Linguistics, modality is the realization of the interpersonal meaning. Many modality analyses have been conducted in political speeches, debates and student’s writing. However, there have been a few comparisons of two talk shows where the same participant interacted with two different power statuses. This article explored with whom and what type of modality Ellen, the host of Ellen Talk Show, used more and the ambiguous situations where it is difficult to decide propositions or proposals. With the theory of Halliday’s Systemic Functional Linguistics (Halliday, 1985; Halliday, 1994; Halliday and Matthiessen, 2004; Eggins, 2004; Halliday and Matthiessen, 2014), the article found out that Ellen used more modality with the teacher (30%) than with the Vice President (17%). Despite she is supposed to communicate in formal language, she chose to speak in an informal way. Secondly, Ellen enjoyed more or less the same probability in two Talk Shows, while two times more obligation and 4 times more inclination with the teacher. Finally, it is significantly found that ambiguous situations can occur when obligation and inclination – ‘have to’ and ‘want to’- are realized in the exchange of information, and probability ‘am going to’ is found in the realization of an offer and ‘can’t’ in a command.